A complementary biocompatibility evaluation of plasma sprayed dentine (DHA) and enamel derived hydroxyapatite (EHA) using fibroblasts - (:unkn) unknown (Trans Tech Publications Ltd, 2006)
Hydroxyapatite (HA) material, collected from human tooth, was calcined and then separated very easily to enamel HA (EHA) and dentine HA (DHA). The EHA and DHA were plasma sprayed on pre-prepared titanium implants. HeLa (a lineage malignant fibroblast cell) and primary fibroblast cells cell lines were used in this study. The results using fibroblasts from primary culture are interesting since the cells did not die or became apoptotic. However, this does not mean that the present method reveals the complete biocompatibility of the tested HA material. This study aimed to investigate if fibroblasts with fluorescent tests could be used as a secondary evaluation method for biocompatibity fibroblasts cell culture studies prior to osteoblasts cell culture.
Keywords: Biocompatibility; Cell culture; Dentine Hydroxyapatite; Enamel Hydroxyapatite; Plasma Spraying